Common Factors of a Transtheoretical Model of Autism Spectrum Disorder-Informed Psychotherapy - Strunz, Ruth M. (Canadian Journal of Counselling and Psychotherapy, 2018)
Individuals with autism spectrum disorder-level 1 (ASD-1, formerly Asperger’s disorder or Asperger’s syndrome) frequently experience relationships as challenging, confusing, or aversive. With the current prevalence of ASD-1 in North America and internationally, there is a pressing need for ASD-informed psychotherapy (ASD-IP). Based in developmental psychology and aligned with the recovery paradigm, this article explores the impact of the common features of ASD-1 on the working alliance as reflective of the individual’s relational experience outside of therapy. This article brings together voices from the literature with those of client and therapist, suggesting key elements of ASD-IP and proposing implications for further research, therapist training, and service delivery.